Overseas Chinese Christian entrepreneurs in modern China : a case study of the influence of Christian ethics on business life - Tong, Joy Kooi-Chin (Key issues in modern sociology., 2012)
Inspired by Max Weber's thesis on the Protestant ethic, this volume examines the influence of Christianity on overseas Chinese entrepreneurs working in China during its transition from a centrally-planned economy toward a market economy under Communist rule.